Pelayanan Koinonia yang Berkualitas dan Implikasinya di Gereja Masa Kini - Megawati Manullang (Publisher STPKat, 2022)
Abstract. The Koinonia ministry is one of the tri-duties of the church's vocation which at this time seems to have begun to weaken quite a number of churches due to the development of the times which requires that the koinonia strategy must be improved or in other words quality. Therefore, a quality Koinonia ministry is able to protect the congregation to remain faithful in fellowship. A good Koinonia is to divide certain categories to improve the quality of the congregation in its growth in quality and quantity. In this paper, I provide Koinonia services by dividing into five categories, namely: Child Category (Age 0-2, 2-5, 6-12), Youth Category (Age 15-35 years), Early Adult Category (Age 17- 22, 22-28, 28-33, 40-45 years), Middle Adult Category (45-65 years old), and Advanced Adult Category (over 60 years old). Each category has its own portion and needs according to their psychological condition and situation, which should be seen from the point of view of their age. This will make it easier for the church to improve or even improve the quality of Koinonia's service to the congregation, especially in today's churches that require an increase in their Koinonia.